Improving specialist palliative care in residential care for older people: a checklist to guide practice. Issue 3 (2nd August 2017) - Forbat, Liz; Chapman, Michael; Lovell, Clare; Liu, Wai-Man; Johnston, Nikki
Abstract : Objectives: Palliative care needs rounds are triage meetings that have been introduced in residential care for older adults to help identify and prioritise care for people most at risk for unplanned dying with inadequately controlled symptoms. This study sought to generate an evidence-based checklist in order to support specialist palliative care clinicians integrate care in residential nursing homes for older people. Methods: A grounded theory ethnographic study, involving non-participant observation and qualitative interviews. The study was conducted at four residential facilities for older people in one city. Observations and recordings of 15 meetings were made, and complimented by 13 interviews with staff attending the needs rounds. Results: The palliative care needs round checklist is presented, alongside rich description of how needs rounds are conducted. Extracts from interviews with needs rounds participants illustrate the choice of items within the checklist and their importance in supporting the evolution towards efficient and effective high-quality specialist palliative care input to the care of older people living in residential care. Conclusions: The checklist can be used to support the integration of specialist palliative care into residential care to drive up quality care, provide staff with focused case-based education, maximise planning and reduce symptom burden for people at end of life.